Familial Follicular Cell-Derived Thyroid Carcinoma - Son, Eun Ju; Nosé, Vania (Frontiers in Endocrinology, 2012)
Follicular cell-derived well-differentiated thyroid cancer, papillary (PTC) and follicular thyroid carcinomas comprise 95% of all thyroid malignancies. Familial follicular cell-derived well-differentiated thyroid cancers contribute 5% of cases. Such familial follicular cell-derived carcinomas or non-medullary thyroid carcinomas (NMTC) are divided into two clinical–pathological groups. The syndromic-associated group is composed of predominately non-thyroidal tumors and includes Pendred syndrome, Warner syndrome, Carney complex (CNC) type 1, PTEN-hamartoma tumor syndrome (PHTS; Cowden disease), and familial adenomatous polyposis (FAP)/Gardner syndrome. Other conditions with less established links to the development of follicular cell-derived tumors include ataxia–telangiectasia syndrome, McCune Albright syndrome, and Peutz–Jeghers syndrome. The final group encompasses syndromes typified by NMTC, as well as pure familial (f) PTC with or without oxyphilia, fPTC with multinodular goiter, and fPTC with papillary renal cell carcinoma. This heterogeneous group of diseases does not have the established genotype–phenotype correlations known as in the familial C-cell-derived tumors or medullary thyroid carcinomas (MTC). Clinicians should have the knowledge to identify the likelihood of a patient presenting with thyroid cancer having an additional underlying familial syndrome stemming from characteristics by examining morphological findings that would alert pathologists to recommend that patients undergo molecular genetic evaluation. This review discusses the clinical and pathological findings of patients with familial PTC, such as FAP, CNC, Werner syndrome, and Pendred syndrome, and the heterogeneous group of familial PTC.